Understanding aerodynamics : arguing from the real physics - McLean, Doug, 1943- (Aerospace series (Chichester, England), 2013)
A real understanding of aerodynamics must go beyond mastering the mathematical formalism of the theories and come to grips with the physical cause-and-effect relationships that the theories represent. In addition, design work depends heavily on voluminous numerical computations. It is more important than ever for a practicing engineer to bring to the task a knowledge solidly based in the physics of aerodynamics.